Impact of three exogenous phosphorus-solubilizing bacteria on zinc and selenium contents and rhizosphere soil nutrients of Longjing and Huangjinya tea plants - Guo, JinMei; Zhang, ShuQing; Li, JianFeng (Frontiers in Microbiology, 2024)
This experiment aimed to investigate the impact of three strains of exogenous phosphorussolubilizing bacteria on soil nutrients as well as the uptake of Zinc and Selenium elements by tea plants. Following the inoculation of potted Longjing and Huangjinya varieties with exogenous phosphorus-solubilizing bacteria, we determined the concentrations of AN, AP, AK, Zn, and Se in their rhizosphere soil, in addition to the Zn and Se contents in their aboveground and belowground parts. The results show that after respective treatment with the three PSB, the concentration of available P in the tea plant rhizosphere soil significantly increased, with PMS08 having the most pronounced effect.After the same treatment, In the rhizosphere soil of Longjing tea plants, the AN content increased by 26.47%, 18.41%, and 7.51%, respectively, relative to the control, while the AK content decreased in the rhizosphere soil of Huangjinya tea plants. Inoculation with the three PSB resulted in a greater content of available Se in both the aboveground and belowground parts of the two tea plants. After inoculation with PMS20, the available Zn content of the belowground parts of Longjing and Huangjinya tea plants respectively decreased by 13.42% and 15.69% in comparison with the control. Additionally, after inoculating Longjing tea plants with PSt09 and Huangjinya tea plants with PMS08, the content of available Zn in their belowground parts significantly decreased by 9.22% and 35.74%, respectively. Evidently, the inoculation with the three phosphorus-solubilizing bacteria is beneficial for the uptake of available P by tea plants, promoting the utilization and accumulation of available Se. However, the content of AN or AK in rhizosphere soil varies between different tea plant varieties inoculated with the same kind of phosphorus-solubilizing bacteria.. Moreover, the content of available Zn in tea plants also differs, highlighting the need to further investigate the differential effects of phosphorus-solubilizing bacteria on different plant varieties.